Influence of the topography of brain damage on depression and fatigue in patients with multiple sclerosis. (February 2014) - Gobbi, C; Rocca, MA; Riccitelli, G; Pagani, E; Messina, R; Preziosa, P; Colombo, B; Rodegher, M; Falini, A; Comi, G; Filippi, M
Objectives: Involvement of selected central nervous system (CNS) regions has been associated with depression and fatigue in MS. We assessed whether specific regional patterns of lesion distribution and atrophy of the gray (GM) and white matter (WM) are associated with these symptoms in MS. Methods: Brain dual-echo and 3D T1-weighted images were acquired from 123 MS patients (69 depressed (D), 54 non-depressed (nD), 64 fatigued, 59 non-fatigued) and 90 controls. Lesion distribution, GM and WM atrophy were estimated using VBM and SPM8. Results: Gender, age, disease duration and conventional MRI characteristics did not differ between D-MS and nD-MS patients. Fatigued patients experienced higher EDSS and depression than non-fatigued ones. Lesion distribution and WM atrophy were not related to depression and fatigue. Atrophy of regions in the frontal, parietal and occipital lobes had a combined effect on depression and fatigue. Atrophy of the left middle frontal gyrus and right inferior frontal gyrus were selectively related to depression. No specific pattern of GM atrophy was found to be related to fatigue. Conclusions: Depression in MS is linked to atrophy of cortical regions located in the bilateral frontal lobes. A distributed pattern of GM atrophy contributes to the concomitant presence of depression and fatigue in these patients.